The Intersection of HIPs, Experiential Learning, and Equity in Higher Education: A values-based contribution to defining experiential education - Davis, Quentin; Pettit, Stacie (Experiential Learning and Teaching in Higher Education, 2024)
Experiential Learning (EXL) and High Impact Practices (HIPs) as concepts and as practices have a great deal in common but are not the same nor are they mutually exclusive. In this paper, we review the intersection and overlap of these two concepts in the context of higher education from the literature and from discussions among faculty and administrators at a Society for Experiential Education conference. Participants discussed the definitions of each concept at their home institutions and generated visual models to represent ways in which EXL and HIP activities overalp. The authors propose two alternative models of conceptualization where learning activities simultaneously exist on continuums of impact and experientiality. We also consider gaps of inclusivity and equity in HIPs and EXL from the literature and participant experiences. Finally the authors make suggestions for how institutions might scale HIPs and EXL in ways that welcome and include all students with equity of access.